The Effect of Binder on Bioceramic Surface Roughness when Milling using Ball Nose End Mill - Suleiman, Amin Suffian; Rafai, Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Nowadays, the increasing number of road accidents has led to a rise since the accidents may result in permanent disability that often require surgical intervention. As a purpose to replace bone, a type of bioceramic which is hydroxyapatite (HAP) is chosen since it is a chemical substance that has similar characteristics to the mineral found in human bone and hard tissues. The water-soluble binder is used to make the substances hold together which is PEG and PVA. Four (4) samples of hydroxyapatite with different amounts of binder are made to examine the effects of binders on the bioceramic mechanical properties. on bioceramic surface roughness when milling using ball nose end mill. The sample is prepared by using dry mixing and compaction method whereas the ratio of PEG and PVA used are from 1% to 4% by weight. After compaction, the samples are sintered in the furnace for a total of 22 hours with 2 hours of soaking period in which the heating and cooling rate is 120 o C/hour. The temperature set for the soaking period is 1200 o C. The HAp sintered body is then machined by CNC milling machine using ball nose end mill cutter with a constant machining parameter of cutting speed, feed rate and depth of cut which is 27m/min, 40mm/rev and 0.1mm. Other than that, the sample undergoes mechanical properties testing such as modulus of rupture, vickers hardness, porosity and density. From the test, it is observed the amount of binder used influences the mechanical properties and surface roughness of the sample. Sample 4 which contains PEG 4 PVA 1 has the highest yield strength, hardness value and surface roughness. Other than that, the highest porosity obtained is sample 3 which contains PEG 3 PVA 2 and sample 4 has the highest density. In conclusion, the hydroxyapatite (HAp) samples with different amounts of binder used influence the sample compatibility and mechanical properties.